Diet-induced obesity exacerbates imiquimod-mediated psoriasiform dermatitis in anti-PD-1 antibody-treated mice: Implications for patients being treated with checkpoint inhibitors for cancer. Issue 3 (March 2020) - Yu, Sebastian; Wu, Xuesong; Shi, Zhenrui; Huynh, Mindy; Jena, Prasant Kumar; Sheng, Lili; Zhou, Yan; Han, Dan; Wan, Yu-Jui Yvonne; Hwang, Samuel T.
Highlights: Diet-induced obesity exacerbates imiquimoid-induced psoriasiform dermatitis in mice. Western diet (WD)-fed mice have more γδ low T cells and more PD-1 expressing γ δ low T cells than control diet-fed mice. WD-fed mice have a more exaggerated response to anti-PD-1 than lean mice in terms of IMQ-induced ear swelling, suggesting obesity could be a risk factor in the development of psoriasiform eruption during anti-PD-1 therapy. Abstract: Background: An ever-increasing number of cancer patients are being treated with checkpoint inhibitors such as anti-PD-1 antibodies, and a small percentage of these patients develop a psoriasis-like skin eruption or severe flares of prior psoriasis. Objective: We investigated the role of obesity in immune checkpoint inhibitors-exacerbated psoriasiform eruption. Methods: We fed female C57BL/6 mice a so-called Western diet (WD) or a control diet (CD). Imiquimod (IMQ) was applied topically on ears for 5 consecutive days to induce psoriasiform dermatitis (PsD). Psoriasis-related markers were examined by quantitative real-time PCR. Then we induced PsD in WD- and CD-fed mice in the presence or absence of systemic treatment of anti-PD-1 antibodies to examine if obese mice are more susceptible to anti-PD-1 related PsD than lean mice. Results: WD-fed mice showed higher baseline mRNA expression levels of psoriasis-associated cytokines such as IL-17, S100A8, and S100A9 compared to mice fed with CD. Furthermore, WD-fed mice had more γ δ low (GDL) T cells in the whole skin and higher expression of PD-1 on GDL T cells than CD-fed mice. WD-fed mice receiving anti-PD-1 had more prominent ear swelling than lean mice receiving anti-PD-1 during the 5-day IMQ course (2-fold increase, P < 0.0001 on day 5). Conclusion: WD-induced obesity enhances IMQ-induced psoriasiform inflammation. The finding that WD-fed mice have a more dramatic response to anti-PD-1 than lean mice in terms of IMQ-induced ear swelling suggests that obesity could be a risk factor in the development of psoriasiform eruption during anti-PD-1 therapy.